2012
DOI: 10.1007/s10295-012-1102-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of poly(3hydroxybutyrate-co-3hydroxyvalerate) production from cane molasses by Azohydromonas lata MTCC 2311 in a stirred-tank reactor: effect of agitation and aeration regimes

Abstract: The effects of agitation and aeration rates on copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] production by Azohydromonas lata MTCC 2311 using cane molasses supplemented with propionic acid in a bioreactor were investigated. The experiments were conducted in a three-level factorial design by varying the impeller (150-500 rev min(-1)) and aeration (0.5-1.5 vvm) rates. Further, the data were fitted to mathematical models [quadratic polynomial equation and artificial neural network (ANN)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…Zafar et al (2012) [45] investigated the modeling and optimization of the poly(3-hydroxybutyrate-co-hydroxyvalerate) production from cane molasses using a bioreactor, and the effect of agitation and aeration regime on Azohydromonas lata MTCC 2311 inoculum, at 180 rpm and 30°C for 24 h. The authors reported a higher P(3HB-co-3HV) productivity of 0.163 g.L − 1 .h − 1 , which is similar to the findings of the present study. However, only the inoculum production conditions can be compared with the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Zafar et al (2012) [45] investigated the modeling and optimization of the poly(3-hydroxybutyrate-co-hydroxyvalerate) production from cane molasses using a bioreactor, and the effect of agitation and aeration regime on Azohydromonas lata MTCC 2311 inoculum, at 180 rpm and 30°C for 24 h. The authors reported a higher P(3HB-co-3HV) productivity of 0.163 g.L − 1 .h − 1 , which is similar to the findings of the present study. However, only the inoculum production conditions can be compared with the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of PHB accumulation in presence of high oxygen could be due to the generated high shear force which was proven to inhibit the PHB biosynthesis by a number of microbes [42,43].…”
Section: Batch Growth In Bioreactormentioning
confidence: 99%
“…The mixture was filtered and treated with 4 volume of cold methanol to precipitate the PHA granules. The precipitates were filtered off and dried at room temperature to get the powder of PHA [32].…”
Section: Extraction and Recovery Of Phamentioning
confidence: 99%
“…The analysis was carried out in an inert gas atmosphere of nitrogen at a flow rate of 100 mL/min in the temperature range from 25 to 350°C with a heating rate of 10°/min. The temperatures of melting and decomposition were determined as the temperature of corresponding endothermic maxima [32].…”
Section: Physico-chemical Characterization Of Isolated Copolymermentioning
confidence: 99%